2015
DOI: 10.1097/01.j.pain.0000461252.75089.bf
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of new-onset distal neuropathic pain in HIV-infected individuals in the era of combination antiretroviral therapy

Abstract: Despite modern combination antiretroviral therapy (CART), distal neuropathic pain (DNP) continues to affect many individuals with HIV infection. We evaluated risk factors for new onset DNP in the CNS Antiretroviral Therapy Effects Research (CHARTER) study, an observational cohort. Standardized, semi-annual clinical evaluations were administered at six U.S. sites. DNP was defined by using a clinician-administered instrument standardized across sites. All participants analyzed were free of DNP at study entry. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…The few studies on HIV-related chronic pain suggest that peripheral neuropathy is a major cause for this pain, affecting an estimated 27% of HIV patients (8). Risk factors for HIV-related neuropathic pain include current or former illicit drug abuse, HIV illness severity, older age, Black race/ethnicity, and use of specific classes of antiretroviral therapy (5, 810).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies on HIV-related chronic pain suggest that peripheral neuropathy is a major cause for this pain, affecting an estimated 27% of HIV patients (8). Risk factors for HIV-related neuropathic pain include current or former illicit drug abuse, HIV illness severity, older age, Black race/ethnicity, and use of specific classes of antiretroviral therapy (5, 810).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for HIV-related neuropathic pain include current or former illicit drug abuse, HIV illness severity, older age, Black race/ethnicity, and use of specific classes of antiretroviral therapy (5, 810). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one high-quality study suggested that asymptomatic SN may transition into symptomatic SN within a 12 to 24-month period on cART. 29 When symptomatic neuropathies developed within our cohort, they developed rapidly (most cases occurring within 3-months of initiating cART, and as early as 2 weeks), compared to asymptomatic neuropathies, which developed more slowly (most cases within ± 5-months of initiating cART). Rapid onset, painful neuropathies have also been reported in cohorts on other cART regimens including stavudine, zidovudine, and zalcitabine.…”
Section: Discussionmentioning
confidence: 72%
“…While the increase in the proportion with asymptomatic neuropathy is welcomed, this finding needs to be regarded with some caution: we only followed individuals for 6 months and so it is not clear if asymptomatic SN remained asymptomatic or whether it may have progressed to being symptomatic. Indeed, one high‐quality study suggested that asymptomatic SN may transition into symptomatic SN within a 12 to 24‐month period on cART . When symptomatic neuropathies developed within our cohort, they developed rapidly (most cases occurring within 3‐months of initiating cART, and as early as 2 weeks), compared to asymptomatic neuropathies, which developed more slowly (most cases within ± 5‐months of initiating cART).…”
Section: Discussionmentioning
confidence: 85%
“…A maioria dos pacientes com HIV sentem dor e usam vários métodos para aliviá-la, mas com analgesia inadequada 63 . A dor neuropática é fortemente influenciada por desordens psiquiátricas 64 . A detecção do tratamento para depressão nos pacientes com dor neuropática distal moderada e grave é importante para o tratamento bem-sucedido dessa alteração 65 .…”
Section: Clínica Do Pacienteunclassified